INFLUENCE OF THE CREATIVE ECONOMY ON MODERN MANAGEMENT OF CREATIVE INDUSTRIES - D. A. Prokofeva; N. V. Shamardina (Вестник университета, 2020)
The features of the modern approach to the organization of working process in creative industries, where the key is the concept of “teal organization” distinctive quality characteristics of which are self-government and self-organization, implying independent implementation of the work processes and projects realization by the employees, have been considered. The rules of creating competent communication with the creative class, people who are the driving force of the creative economy, play an essential role in organizing the management of creative industries in modern society. The functioning of “teal organizations” exclusively within the framework of a creative economy, where the greatest value is the realization of the creative potential of the employee, has been examined in the article.